Tafsiran Quran dalam persepktif jaringan Islam liberal - Muhd. Najib Abdul Kadir; Muhibudin Hassan; Mazlan Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2007)
The Islamic Liberal Networking (ILN) has emerged within Muslim societies since 1970s to spread the deviating notions among Muslims. In Indonesia, there have been new types of the Qur'anic exegeses and one of them is the Qur'anic exegesis by the advocates and exponents of Islamic liberalism. Their opponents have viewed their Qur'anic exegesis as a heretical type of exegesis because they depend or rely on the liberal methods to interpret the Qur'anic verses and the texts of the Prophetic tradition. Based on the library research method, this study discusses the history of the heretical exegesis of the Qur'an and its methods including the Qur'anic exegesis made by the advocates and exponents of Islamic liberalism through their Islamic liberal networking. Through this study, it has been discovered that their Qur'anic exegesis diametrically contradicts the al-ma'thiir Qur'anic exegesis. Therefore, their Qur'anic exegesis is dangerous and heterodox because it leads to the rejection of some Islamic fundamental teachings and beliefs